Genesis 1:26-7 as a statement of humanity’s divine parentage - Crouch, C.L. (Oxford University Press, 2010)
The linguistic and cultural background of the words tslm and dmwt supports a reading of Gen. 1:26–7 as a statement of humanity’s divine parentage. As such it is intended to evoke the responsibilities of child to parent and of parent to child in the minds of its readers. Such an interpretation accommodates both the semantic range of the key terms tslm and dmwt and the sense that the statement is meant to be theologically significant.